1972
DOI: 10.1001/archneur.1972.00490130003001
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sympathetic Nervous Activity on Cerebral Blood Flow

Abstract: The effect on the cerebral blood flow (CBF) (27:1-6,1972)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
90
4
3

Year Published

1973
1973
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(110 citation statements)
references
References 12 publications
12
90
4
3
Order By: Relevance
“…Thus, to the extent that the renal SNA may also reflect sympathetic activity to the well-innervated circle of Willis and large cerebral arteries, the late CVR increase may be a consequence of increased sympathetic discharge also to these vessels, whereas the initial CVR decrease would reflect the combined effects of 'myogenic' autoregulatory va sodilatation, accumulation of local vasodilatatory substances and reduced sympathetic vasoconstric tor activity. It has been shown by Harper et al (1972) and Fitch et al (1975) that increased SNA to the circle of Willis and large cerebral arteries can shift the lower autoregulatory limit to higher pres sure levels and thereby further decrease CBF, if MABP is already below the lower autoregulatory limit for CBF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to the extent that the renal SNA may also reflect sympathetic activity to the well-innervated circle of Willis and large cerebral arteries, the late CVR increase may be a consequence of increased sympathetic discharge also to these vessels, whereas the initial CVR decrease would reflect the combined effects of 'myogenic' autoregulatory va sodilatation, accumulation of local vasodilatatory substances and reduced sympathetic vasoconstric tor activity. It has been shown by Harper et al (1972) and Fitch et al (1975) that increased SNA to the circle of Willis and large cerebral arteries can shift the lower autoregulatory limit to higher pres sure levels and thereby further decrease CBF, if MABP is already below the lower autoregulatory limit for CBF.…”
Section: Discussionmentioning
confidence: 99%
“…whereas the intraparenchymal vessels constricted initially but then began to dilate and exceeded the control level at the later stage de spite continued stimulation. Harper et al (1972) hypothesized that sympathetic constriction of the extraparenchymal vessels might be compensated for by secondary dilation of the intraparenchymal vessels elicited by a chemical control. Busija et al (19tl2) measured the blood flow velocity of the pial arteries and indicated that constriction of the pial arteries during sympathetic nerve stimulation was accompanied by an increase in the intravascular blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy seems to depend partly on the method ological limitations of measuring CBF and on the homeostatic mechanism of cerebral circulation. Harper et al (1972) hypothesized that under most circumstances, sympathetic constriction of the ex traparenchymal and pial vessels might be com pen- …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This means that it may be difficult to consider the cerebrovascular bed as consisting of components in series which are principally regulated by either neural or metabolic factors. 8 Nor is it in dispute that in morphological terms the adrenergic terminals are identical to those seen in other vascular beds and effector organs. They approximate to within 80 9 to 300 nm 1011 of the adventitial border of smooth muscle.…”
Section: Areas Of Uncertainty Concerning the Neuralmentioning
confidence: 99%